Fluorescence quenching of optical fiber chemical sensor detecting hazardous dinitrobenzene material - Yusufu, Abdullahi Magaji (2017)
The consistent explosive and hazardous material monitoring is among the demanding aspect of security due to global terrorism activities in this era. Fluorescence sensing technology is among the best promising methods used for explosive detection nowadays because of its numerous advantages, which include simplicity of instrument, high sensitivity and short response time. This dissertation presents the development of optical fiber chemical sensors for detection of an explosive material 1, 4-dinitrobenzene (DNB) in acetone. Two polymers have been chosen to detect the explosive material. Chitosan polymer and conjugated polymer poly[2-methoxy-5-(2'-ethylhexyloxy)-p-phenylenevinylene (MEH-PPV) based optical fiber sensors are fabricated by modifying the fibers to enable a good formation of the polymer matrix on the sensing regions. First, a multi-mode fiber is tapered and the chitosan polymer is modified by cross-linking with glutaraldehyde to detect DNB in solution. The solution is deposited on the optical fiber tapered region to create a sensing portion using dip-coating method. Whereas, the conducting polymer MEH-PPV based sensors are developed by dip coating the tip of plastic optical fibers to detect the DNB as well. Unlike other fiber sensor developments, this study takes cognizance of fluorophore concentration in solvent for accessing the quenching ability of the analyte to improve sensitivity and performance of optical fiber sensors. Several chitosan and MEH-PPV polymer amount in solvents were characterized using UV-Vis and fluorescence intensity spectroscopy before coating processes. The morphology of cross-linked chitosan is done using scanning electron microscope (SEM). To characterize the changes in optical property due to modification of chitosan, ultraviolet (UV) laser and ultrafast femtosecond laser sources are used. DNB concentration as low as 1ppm is detected when it was introduced to the chitosan based optical sensor. Time-dependent quenching results indicated that the sensor could operate in both linear and nonlinear regions with rapid quenching for nonlinear excitation source. For MEH-PPV based plastic optical fiber fabricated sensors, the developed devices are tested for DNB sensitivity and quenching ability with respect to time in terms of fluorophore amount in solvent. Preliminary results indicated that the initial fluorescence intensity generated increases with decrease of polymer/fluorophore concentration in solvent. This behavior is observed once more when sorted MEH-PPV samples are deposited as thin films on the plastic fiber tip to create a sensing region. When the sensors are introduced to 5ppm DNB in acetone for 10 seconds, there is a significant decrease of fluorescence intensity for sensor with thinner coating than that with thicker coating. This indicates that fluorescence of MEH-PPV can be quenched effectively in thinner films than in thicker films. All the developed sensors show high sensitivity and fast response with detection limit of 1.635ppm. The enhancement of sensing capability of DNB is explored using fluorophore amount in solvent and Stern-Volmer quenching analysis have been used to investigate their kinetic reaction.